Solar tracker for enhancement of the thermal efficiency of solar water heating system. (April 2018) - Abdelghani-Idrissi, M.A.; Khalfallaoui, S.; Seguin, D.; Vernières-Hassimi, L.; Leveneur, S.
Abstract: This paper deals with thermal efficiency enhancement analysis of a solar water heating system with a solar tracker. Made at laboratory-scale, an automated mechanical system enables solar panel rotation and inclination. The control system is programmed to place the solar panels facing the sun throughout the day. Its coordinates by means of the solar height and the azimuthal angle will determine the sun position on the celestial sphere. The thermal behaviour of the solar water heating system is developed with energy balance on solar panels, heat exchanger and storage system. The solar irradiation intensity is measured by a pyranometer placed in the plan of the solar panels. Comparison between experimental results obtained for fixed inclinations of solar panels and those obtained with the solar tracker shows a 40% gain of overall stored thermal energy. The energy gain depends on the season. The low inclinations are still favourable in summer while in winter they are higher inclinations are needed. Highlights: Thermal efficiency enhancement analysis of a solar water heating system with a solar tracker. The solar panel positioning is determined according to the sun height and azimuthal angle. The thermal behaviour of the solar water heating system is developed with energy balance on solar panels, heat exchanger and storage system. Comparison between results obtained for fixed inclinations of solar panels and those obtained with the solar tracker shows a 49% gain of overall stored thermal energy.